A novel substrate directed multicomponent reaction for the syntheses of tetrahydro-spiro[pyrazolo[4, 3-f]quinoline]-8, 5′-pyrimidines and tetrahydro-pyrazolo[4, 3-f]pyrimido[4, 5-b]quinolines via selective multiple C–C bond formation under metal-free conditions. Issue 33 (22nd May 2020) - Patel, Divyang M.; Patel, Hetal J.; Padrón, José M.; Patel, Hitendra M.
Abstract : Substrate selectivity in the novel multi-component reaction of 5-aminoindazole, barbituric acid derivatives and aldehyde is explored. Abstract : A versatile and substrate oriented multicomponent reaction for the syntheses of novel highly diastereoselective tetrahydro-1′ H -spiro[pyrazolo[4, 3- f ]quinoline-8, 5′-pyrimidine]-2′, 4′, 6′(3′ H )-triones (d.r. up to 20 : 1 ( syn : anti )) and tetrahydro-8 H -pyrazolo[4, 3- f ]pyrimido[4, 5- b ]quinoline-8, 10(9 H )-diones via formation of selective multiple C–C bonds under identical reaction conditions ( viz. ethanol as a reaction medium and deep eutectic mixture as a catalyst) is demonstrated. Both approaches involve mild reaction conditions, use of non-hazardous solvents, and facilitate good to excellent reaction yields of the target compounds.